A method of improving the dynamic response of 3D force/torque sensors. (February 2016) - Osypiuk, Rafał; Piskorowski, Jacek; Kubus, Daniel
Abstract: In the paper attention is drawn to adverse dynamic properties of filters implemented in commercial measurement systems, force/torque sensors, which are increasingly used in industrial robotics. To remedy the problem, it has been proposed to employ a time-variant filter with appropriately modulated parameters, owing to which it is possible to suppress the amplitude of the transient response and, at the same time, to increase the pulsation of damped oscillations; this results in the improvement of dynamic properties in terms of reducing the duration of transients. This property plays a key role in force control and in the fundamental problem of the robot establishing contact with rigid environment. The parametric filters have been verified experimentally and compared with filters available for force/torque sensors manufactured by JR3. The obtained results clearly indicate the advantages of the proposed solution, which may be an interesting alternative to the classic methods of filtration. Abstract : Highlights: The proposed mechanism is based on the variation of the filter parameters during the transition phase. We examine the impulse and step responses of the JR3 force/torque sensor in a specially prepared experimental setup. Time-varying approach offers a significant improvement in dynamic properties of force/torque sensors. A significant reduction in time-delay has been obtained, which plays a key role in the closed-loop force control.